2018
DOI: 10.1038/s41467-018-06462-0
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced adaptive thermogenesis requires neuropeptide FF receptor-2 signalling

Abstract: Excess caloric intake results in increased fat accumulation and an increase in energy expenditure via diet-induced adaptive thermogenesis; however, the underlying mechanisms controlling these processes are unclear. Here we identify the neuropeptide FF receptor-2 (NPFFR2) as a critical regulator of diet-induced thermogenesis and bone homoeostasis. Npffr2−/− mice exhibit a stronger bone phenotype and when fed a HFD display exacerbated obesity associated with a failure in activating brown adipose tissue (BAT) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 72 publications
(109 reference statements)
4
62
0
Order By: Relevance
“…The subpostrema, a V-shaped area, is located adjacent to the AP and on the upper limit of the commissural part of the NTS; it too is involved in autonomic regulation and provides bidirectional connections between area postrema and the NTS (78). Recently, Zhang et al determined that Neuropeptide FF receptor 2 (Npffr2) signaling regulated NPY neuron activity in the arcuate nucleus and influenced BAT activity via the PVH (79). In addition to Npffr2 expression in the ARC, retrograde tracing from the ARC demonstrated that brainstem regions such as the area postrema, subpostrema, and NTS could provide input and regulate ARC neurons (79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subpostrema, a V-shaped area, is located adjacent to the AP and on the upper limit of the commissural part of the NTS; it too is involved in autonomic regulation and provides bidirectional connections between area postrema and the NTS (78). Recently, Zhang et al determined that Neuropeptide FF receptor 2 (Npffr2) signaling regulated NPY neuron activity in the arcuate nucleus and influenced BAT activity via the PVH (79). In addition to Npffr2 expression in the ARC, retrograde tracing from the ARC demonstrated that brainstem regions such as the area postrema, subpostrema, and NTS could provide input and regulate ARC neurons (79).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al determined that Neuropeptide FF receptor 2 (Npffr2) signaling regulated NPY neuron activity in the arcuate nucleus and influenced BAT activity via the PVH (79). In addition to Npffr2 expression in the ARC, retrograde tracing from the ARC demonstrated that brainstem regions such as the area postrema, subpostrema, and NTS could provide input and regulate ARC neurons (79). Npffr2 deficient mice on a high fat diet show increased adiposity, reduced whole body energy expenditure, reduced UCP-1 protein in BAT and increases in cancellous bone mass (79).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an increase in white adipose tissue leads to an increase in functional active brown adipose tissue, which lowers the energetic efficiency of feeding. The increase in energy-expenditure that results from diet-induced adaptive thermogenesis is mediated via a recently discovered hypothalamic NPY-dependent circuitry, which signals independent of the cold-induced BAT thermogenesis activation ( Zhang L. et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, the activity of A1/C1 catecholaminergic neurons in the ventrolateral medulla associated with sympathetic ganglia is reduced, resulting in reduced sympathetic nerve outflow to peripheral tissues (e.g., BAT) ( 8 ). A study showed that the neuropeptide FF receptor 2 (NPFFR2) signal directly acts on ARC NPY neurons ( 104 ). Lack of this NPFFR2-induced tone on NPY neurons reduces the capacity of these neurons to control TH+ neurons in the PVN, with a consequent reduction in BAT function.…”
Section: Npy Indirectly Regulates the Immune Responsementioning
confidence: 99%